The frugal investor : how to build a low-risk, high-return portfolio - Spiering, Scott (AMACOM, 1995)
This guide explains how to cut securities acquisition costs to the absolute bone in four basic asset classes: cash equivalents, domestic equities, fixed-income securities, and international securities. It is the first book to combine value-oriented investing tips with the techniques of multiasset allocation - without question the coming trend in private investing. Read The Frugal Investor for step-by-step instructions on acquiring, holding, reallocating, and liquidating a multiasset portfolio at the minimum cost. Spiering supplies specific product recommendations and, just as important, lists products the average investor may not want to get involved with - such as real estate, collectibles, precious metals, and exotic investments.